Fall downs should not fall out: Blunt cerebrovascular injury in geriatric patients after low-energy trauma is common. Issue 6 (June 2019) - Flashburg, Erika; Ong, Adrian W.; Muller, Alison; Sherwood, Alicia; Wilhelm, Sara; Zavilla, Jared; Martin, Anthony P.; Castor, Laura; Barbera, Spencer C.; Reinhart, Reid; Layser, Shane; McBride, William C.; et al.
Abstract : BACKGROUND: There are limited data examining the impact of screening for blunt cerebrovascular injury (BCVI) in the geriatric population sustaining falls. We hypothesize that BCVI screening in this cohort would rarely identify injuries that would change management. METHODS: A retrospective study (2012–2016) identified patients 65 years or older with Abbreviated Injury Scores for the head and neck region or face region of 1 or greater after falls of 5 ft or less. Patients who met the expanded Denver criteria for BCVI screening were included for analysis. Outcomes were change in management (defined as the initiation of medical, surgical or endovascular therapy for BCVI), stroke attributable to BCVI, in-hospital mortality and acute kidney injury. Univariate analysis was performed where appropriate. A p value less than 0.05 was considered significant. RESULTS: Of 997 patients, 257 (26%) met criteria for BCVI screening after exclusions. The BCVI screening occurred in 100 (39%), using computed tomographic angiography for screening in 85% of patients. Patients who were not screened (n = 157) were more likely to be on preinjury antithrombotic drugs and to have worse renal function compared with the screened group. There were 23 (23%) BCVIs diagnosed in the screened group while one (0.7%) in the nonscreened group had a delayed diagnosis of BCVI. Of the 24 patients with BCVI, 15 (63%) had a change in management, consisting of the initiation of antiplatelet therapy. Comparing the screened to the nonscreened groups, 14% versus 0.7% ( p < 0.0001) had a change in management. The screened group had a higher 30-day stroke rate (7% vs. 1%, p = 0.03) but there were no differences in the stroke rate attributable to BCVI (1% vs. 0.7%, p = 0.99), mortality (6% vs. 8%, p = 0.31) or acute kidney injury (5% vs. 6%, p = 0.40). CONCLUSION: In geriatric patients with low-energy falls meeting criteria for BCVI screening, BCVIs were commonly diagnosed when screened, and the majority of those with BCVI had a change in management. These findings support BCVI screening in this geriatric cohort. LEVEL OF EVIDENCE: Therapeutic/care management, level IV.